Future imperfect contemporary art practices and cultural institutions in the Middle East - Downey, Anthony ca. 20. Jh (Sternberg Press, 2016)
Future Imperfect critically examines the role played by cultural institutions in producing present-day and future contexts for the production, dissemination, and reception of contemporary art in the Middle East and North Africa. It offers critical contexts for a discussion that has become increasingly urgent in recent years - the role of culture in a time of conflict and globalization - and an in - depth critique of the historical state of cultural institutions in an age of political upheaval, social unrest, exuberant cultural activity, ascendant neoliberal forms of privatization, social activism, and regional uncertainty. Based on collective input from numerous contributors and interlocutors, this volume brings together internationally renowned academics, critics, activists, filmmakers, artists, and other independent cultural practitioners to consider how new infrastructures and institutions can effectively emerge within such fraught and dynamic contexts
"Ibraz" is the research and publishing initiative of the Kamel Lazaar Foundation
Keywords: Geschichte 2000-2016; Kunst; Kulturinstitut; Naher Osten; Nordafrika; Aufsatzsammlung